THE INFLUENCE OF USING CUE CARDS IN THE PEER GROUP ACTIVITIES AND LEARNING MOTIVATION TOWARDS SEVENTH GRADE STUDENTS’ READING COMPREHENSION OF NARRATIVE TEXTS AT JUNIOR HIGH SCHOOL 3 PALEMBANG - Nevy Aflidayanti (Esteem Journal of English Education Study Programme, 2022)
The main objective of this study to find out whether or not there was any significant effect on the eight grade students’ learning motivation toward the reading ability after being taught by using cue card. the population of  this  study was the eight grade students at Junior High School Palembangin academic 2021/2022. The total number of the population was 150 students, The sample consisted of 30 students of R1 and 30 students of R2. The method of the study was the experimental method and the data were  collected  through  written  test  in  multiple  choice  form.  The test was administrated twice as the pre-test and post-test. The result were analyzed by using t-test. The students’ Mean score of pretest and post-test in control class of R1 were 53,13 and 73,30. While  the  students’ Mean score  of  Pretest and post  test  in  experimental class of  R2 were 47,50 and 66,33.  The  null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted.